Analysis Of The Behavior Of Using Mobile Banking Services In North Sumatra Students With The Approach: Technology Acceptance Model - Hasibuan, Abdul Nasser; Hardana, Ali; Arif, Muhammad; Siregar, Sulaiman Efendi (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2024)
This study aims to explain the behavioral analysis of the use of mobile banking services to students in North Sumatra with the approach: technology acceptance models, either simultaneously or partially. The sample used is 450 student respondents with the sampling technique using the proportional stratified random sampling technique by conducting a relationship test with the SEM (Structural Equation Model) analysis technique, which will be analyzed using the structural equation modeling tool with the alternative method of partial least square using the SmartPLS software. This study found that simultaneously the perceived usefulness and perceived ease of users have an influence on the behavior of using mobile banking services among students in North Sumatra. Meanwhile, partially, the perceived usefulness and perceived ease of users also have an influence on the behavior of using mobile banking services among students in North Sumatra. As well as the perception of benefits is more dominant than the perceived ease of users in using mobile banking services for students in North Sumatra.Keywords: Usefulness, Ease Of Use, Mobile Banking Usage Behavior